Bovine Blood Constituents as Fat Replacers in Ham Pâté - Fabiana Ribeiro Viana; Carolina Schaper Bizzotto; Disney Ribeiro Dias; Afonso L. Oliveira; Marialice Pinto Coelho Silvestre (Food Technology and Biotechnology, 2004)
Some tests were carried out in this work with the aim of evaluating a partial replacement of fat in the raw batter of ham pâté by using bovine blood constituents, such as globin (GL), plasma (PL) or 1:1 globin and plasma (GP). Plasma was separated from red cells by blood centrifugation, and globin was extracted by the carboxymethylcellulose method. The salt-soluble protein content (SSP) and the binding properties including water holding capacity (WHC) and raw batter stability (RBS) were estimated. The results indicated that among the 3 treatments studied, the use of globin showed to be a little more advantageous for the quality of the raw batter of ham pâté, since its incorporation as fat replacer led to an increase in RBS but no change of SSP was observed.